2002
DOI: 10.1002/ijc.10902
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐19 is expressed by proliferating epithelium but disappears with neoplastic dedifferentiation

Abstract: MMP-19 (also designated RASI) is a recently discovered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
67
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 38 publications
9
67
3
Order By: Relevance
“…42 MMP-19 was widely expressed by keratinocytes at the basal epidermal layer of keratoacanthomas and sporadically in 40% of the SCCs. We and others have previously reported that MMP-19 is absent from invasive cancer cell nests of well-differentiated SCC, 14,34 and our new findings support these results. Thus, the loss of MMP-19 from basal epithelial cells of keratoacanthomas might serve as a warning sign of cancer development.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…42 MMP-19 was widely expressed by keratinocytes at the basal epidermal layer of keratoacanthomas and sporadically in 40% of the SCCs. We and others have previously reported that MMP-19 is absent from invasive cancer cell nests of well-differentiated SCC, 14,34 and our new findings support these results. Thus, the loss of MMP-19 from basal epithelial cells of keratoacanthomas might serve as a warning sign of cancer development.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly MMP-1, -2, -7, -9, -13, -14, and -26 have been shown to be present in well-differentiated cutaneous SCC. [10][11][12] Paradoxically, recent data show that some novel MMPs are in fact instrumental for normal keratinocyte proliferation (MMP-19 and -28) and disappear in cancer, 13,14 whereas MMP-3, -7, -9, and -12 effectively cleave plasminogen to angiostatin and type XVIII collagen to endostatin, leading to inhibition of angiogenesis and eventually retardation of tumor growth. 15,16 Our recent results suggest that epithelial expression of MMP-7, -12, and -13, but not that of MMP-1, -3, -8, -9, and -10, in chronic wounds provides a diagnostic clue for distinguishing welldifferentiated SCCs from nonmalignant wounds.…”
mentioning
confidence: 99%
“…12 On the other hand, MMP19 is down-regulated or lost during neoplastic progression in breast, skin, and colon cancers. [14][15][16] The MMP19-deficiency mouse model showed MMP19 exhibited decreased tumor angiogenesis and invasion. 17 In NPC, Lu et al (2003) screened the expression of a set of MMPs in NPC tissues; MMP19 is down-regulated in NPC tissues as compared to normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…13 In contrast to most MMPs, MMP19 is expressed in many types of normal tissues such as lung, pancreas, placenta, ovary, spleen, intestine, breast, and skin, but is down-regulated or lost during neoplastic progression in breast, skin, and colon carcinomas. 6,[14][15][16] In MMP19-deficient mice, increased tumor angiogenesis and invasion were observed. 17 These findings suggest MMP19 may play a possible role during malignant transformation.…”
mentioning
confidence: 99%
“…In resting adult skin, most MMPs are not constitutively expressed in keratinocytes, with the exception of MMP-7 (matrilysin) in eccrine sweat gland epithelium, MMP-2 (gelatinase A) in occasional basal keratinocytes, MMP-19, tolloid, and tolloid-like 1. However, several MMPs are induced or up-regulated in keratinocytes in the context of inflammation, embryogenesis, and tissue repair/ remodeling, including MMP-1, MMP-2, MMP-3, MMP-9, MMP-10, and MMP-19 (Kahari and Saarialho-Kere, 1997;Rattenholl et al, 2002;Impola et al, 2003;Kerkela and Saarialho-Kere, 2003;Sadowski et al, 2003;Veitch et al, 2003). Unstimulated NHKs in culture produce modest amounts of MMP-1, MMP-2, and MMP-9, but little MMP-10 or MMP19 (Varani et al, 1995a;Kahari and Saarialho-Kere, 1997;Impola et al, 2003;Kerkela and Saarialho-Kere, 2003;Sadowski et al, 2003).…”
mentioning
confidence: 99%